The Ahmed shunt versus the Baerveldt shunt for refractory glaucoma: a meta-analysis - Wang, Shiming (BMC Ophthalmol, 2016)
BACKGROUND: The purpose of this study was to compare the efficacy and tolerability of the Ahmed glaucoma valve (AGV) implant and the Baerveldt implant for the treatment of refractory glaucoma. METHODS: We comprehensively searched four databases, including PubMed, EMBASE, Web of Science, and the Cochrane Library databases, selecting the relevant studies. The continuous variables, namely, intraocular pressure reduction (IOPR) and a reduction in glaucoma medication, were pooled by the weighted mean differences (WMDs), and the dichotomous outcomes, including success rates and tolerability estimates, were pooled by the odds ratio (ORs). RESULTS: A total of 929 patients from six studies were included. The WMDs of the IOPR between the AGV implant and the Baerveldt implant were 1.58 [95 % confidence interval (CI): −2.99 to 6.15] at 6 months, −1.01 (95 % CI: −3.40 to 1.98) at 12 months, −0.54 (95 % CI: −4.89 to 3.82) at 24 months, and −0.47 (95 % CI: −3.29 to 2.35) at 36 months. No significant difference was detected between the two groups at any point in time. The pooled ORs comparing the AGV implant with the Baerveldt implant were 0.51 (95 % CI: 0.33 to 0.80) for the complete success rate and 0.67 (95 % CI: 0.50 to 0.91) for qualified success rate. The Baerveldt implant was associated with a reduction in glaucoma medication at −0.51 (95 % CI: −0.90 to −0.12). There were no significant differences between the AGV implant and the Baerveldt implant on the rates of adverse events. CONCLUSIONS: The Baerveldt implant is more effective in both its surgical success rate and reducing glaucoma medication, but it is comparable to the AGV implant in lowering IOP. Both implants may have comparable incidences of adverse events.